Obesity and associated health related factors among university staff in Serdang, Malaysia - Gyanchand Rampal, Lekhraj Rampal; Saeedi, Pouya; Bezenjani, Somayeh Aminzadeh; Md Said, Salmiah; Othman, Norlijah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2012)
Obesity is a well-established risk factor for coronary heart disease, ischemic stroke, type 2 diabetes, cancers of the breast, colon, prostate and other organs. Objectives: To determine the prevalence of obesity and associated factors among university staffs. Methods: A cross sectional study was carried out among university staffs of University Putra Malaysia using a self-administered validated pre-tested questionnaire. Weight was measured using a digital bathroom scale (TANITA Model HD 319) and height was measured using a SECA Body Meter Model 206. Body mass index (BMI) was calculated as weight in kilograms divided by the square of height in meters (kg/m2). A p value of <0.05 was considered to be statistically significant. Overweight was defined as a body mass index (BMI) of 25 to 29.9 kg/m2 and obesity as a BMI of equal or more than 30 kg/m2. Results: The mean age of the 454 university staffs was 42.86 years. The overall mean BMI was 24.52 ± 4.43 kg/m2, ranged 16.12 to 36.57 (25.69 ± 3.69 kg/m2 for males and 23.31 ± 4.81 kg/m2 for females). The prevalence of overweight and obesity was 31.1% (40.3% males and 21.5% females) and 11.8% (12.1% males and 11.7% females) respectively. After adjusting for all the variables in the logistic regression model, gender, age, occupation, smoking, alcohol intake and physical inactivity were the main predictors of obesity. Conclusions: The prevalence of overweight and obesity is very high among the university staffs. There is a need for a comprehensive integrated non-communicable disease prevention program. There is also a need to establish proactive networks for building up capacity in research and training, mobilizing contributions from within the country and overseas.